2010
DOI: 10.1007/s00018-010-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific and hypoxia-dependent regulation of human HIF-3α: inhibition of the expression of HIF target genes in vascular cells

Abstract: Hypoxia-inducible factors (HIF) are transcription factors responding to reduced oxygen levels and are of utmost importance for regulation of a widespread of cellular processes, e.g., angiogenesis. In contrast to HIF-1α/HIF-2α, the relevance of HIF-3α for the regulation of the HIF pathway in human vascular cells is largely unknown. HIF-3α mRNA increases under hypoxia in endothelial and vascular smooth muscle cells. Analysis of HIF-3α isoforms revealed a cell type-specific pattern, but only one isoform, HIF-3α2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 55 publications
8
49
1
Order By: Relevance
“…The double P393A/P493A mutant behaved essentially the same as the P493A single mutant, suggesting that P493 is more critical for Hif-3␣ stability regulating (56). pVHL recognizes human HIF-1␣ at L574, which is required for human HIF-1␣ instability (1). When the corresponding residue in zebrafish Hif-3␣ (L503) is mutated together with P493 and P393, it resulted in a further increase in Hif-3␣ protein levels, suggesting that L503 contributes to the instability of zebrafish Hif-3␣1 under normoxia (56).…”
Section: Regulation Of Hif-3␣ Expression and Activitymentioning
confidence: 86%
See 1 more Smart Citation
“…The double P393A/P493A mutant behaved essentially the same as the P493A single mutant, suggesting that P493 is more critical for Hif-3␣ stability regulating (56). pVHL recognizes human HIF-1␣ at L574, which is required for human HIF-1␣ instability (1). When the corresponding residue in zebrafish Hif-3␣ (L503) is mutated together with P493 and P393, it resulted in a further increase in Hif-3␣ protein levels, suggesting that L503 contributes to the instability of zebrafish Hif-3␣1 under normoxia (56).…”
Section: Regulation Of Hif-3␣ Expression and Activitymentioning
confidence: 86%
“…It was reported that Hif-2␣ mediated hypoxiainduced Hif-3␣ gene expression in murine 3T3-L1 cells (13). Augstein et al (1) showed that human HIF-3␣2 mRNA expression in human umbilical venous endothelial cells (HUVECs) is induced by hypoxia and this hypoxic induction involves both HIF-1␣, HIF-2␣, and other factors. There is also evidence that several hypoxia-inducible miRNAs may mediate the hypoxia-induced HIF-3␣ gene expression (6).…”
Section: Regulation Of Hif-3␣ Expression and Activitymentioning
confidence: 99%
“…HIF-1α and HIF-2α are often overexpressed in cancer tissue, leading to progression of aggressive tumors, tumor resistance to chemotherapy and radiation, and poor prognosis of the disease (14)(15)(16)(17). The role of HIF-3α in tumors types remains to be elucidated, however, previous studies have indicated that HIF-3α may suppress the expression of genes, which are typically inducible by HIF-1α and HIF-2α in tumor cells (13,18). Therefore, HIF-3α has transcriptional regulatory functions and is a negative regulator of gene expression during hypoxia (13,18).…”
Section: Introductionmentioning
confidence: 99%
“…The role of HIF-3α in tumors types remains to be elucidated, however, previous studies have indicated that HIF-3α may suppress the expression of genes, which are typically inducible by HIF-1α and HIF-2α in tumor cells (13,18). Therefore, HIF-3α has transcriptional regulatory functions and is a negative regulator of gene expression during hypoxia (13,18). Furthermore, HIF-3α is a true transcription factor since it actively stimulates the expression of a number of target genes (19).…”
Section: Introductionmentioning
confidence: 99%
“…The marked downregulation of these genes once again provided evidence that inflammation and basement membrane degradation are suppressed in NF1 patients, which may reduce the risk of tumor metastasis. HIF3α acts as a negative regulator of hypoxia, so it may induce the tolerance of the extracellular environment (13). Whether HIF3α is involved in promoting nerve growth remains to be verified.…”
mentioning
confidence: 99%